2020
DOI: 10.47577/tssj.v8i1.642
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Service Quality and User Value on the Satisfaction and Loyalty of Users at Library and Archives of Padang City

Abstract: This study aims to determine and analyze the effect of service quality and user value on the satisfaction and loyalty of users at the Padang City Library and Archives Service. The sample used was 100 respondents. The sampling technique is purposive sampling. The data is processed using SPSS 16. The type of data used is primary data by distributing questionnaires. Data analysis method with path analysis technique. The results of the study found that the quality of service had a significant effect on the loyalty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…It would enrich the breadth of exploration of relationships between quality dimensions and library success. Hayati and Heryanto (2020) found that users were satisfied with the services being provided by the Library and Archive Department of Padang City, Indonesia, due to the directly positive and significant effect of user value on user satisfaction. Similarly, quality of service had a direct impact on user satisfaction and the user value had a significant effect on user loyalty.…”
Section: Libqual and Library Service Qualitymentioning
confidence: 99%
“…It would enrich the breadth of exploration of relationships between quality dimensions and library success. Hayati and Heryanto (2020) found that users were satisfied with the services being provided by the Library and Archive Department of Padang City, Indonesia, due to the directly positive and significant effect of user value on user satisfaction. Similarly, quality of service had a direct impact on user satisfaction and the user value had a significant effect on user loyalty.…”
Section: Libqual and Library Service Qualitymentioning
confidence: 99%
“…Thus, library management must be carried out properly and systematically so that the services provided are in accordance with the needs of its users (Rochmah, 2016). So, directly quality of service has an influence on user satisfaction (Hayati & Heryanto, 2020).…”
Section: Introductionmentioning
confidence: 99%